"Hey, I'm still here!": Maintaining, managing and rebuilding social connections after brain tumour. Issue 3 (16th March 2023) - Cubis, Lee; Ownsworth, Tamara; Pinkham, Mark B.; Foote, Matthew; Green, Heather; Chambers, Suzanne
ABSTRACT: It is well recognized that social networks can buffer the adverse effects of chronic illness on psychological wellbeing. However, the functional impairments associated with brain tumour often affect social participation, which may reduce people's capacity to draw upon their social capital for support. This qualitative phenomenological study aimed to understand how brain tumour influences people's ability to manage, maintain, and rebuild their social networks. Participants were 20 individuals (65% female) aged 22–69 years with diverse types of primary brain tumour (50% high grade or malignant) who were on average 35 months post-diagnosis. Two semi-structured interviews, conducted three months apart, comprised a Social Identity Mapping exercise and questions exploring changes in social groups since diagnosis. Two overarching and interrelated themes emerged: engaging and connecting and then versus now . An interplay of barriers, facilitators and strategies influenced people's ability to engage and connect with their social groups, which in turn influenced whether they experienced stability; maintenance and expansion; loss and rebuilding; or loss and shrinkage of their social networks over time. These novel findings highlight the need to develop interventions that specifically focus on enhancing individuals' abilities to maintain or rebuild their social networks.